Molecular characterization of Giardia duodenalis cysts in the Oreto River (Sicily, Southern Italy) (Italian Journal of Public Health, 2010)
Background: The presence of Giardia was investigated along the Oreto river between January 2008 and May2009 with the aim of understanding the source of contamination by molecular typing of cysts.Methods: A total of 38 water samples (10 collected from the river mouth, 24 from the whole Oreto basin and4 sewage samples from the Monreale treatment plant) were processed. In addition, 22 faecal samples oflivestock living close to the Oreto area, were analyzed. The presence of Giardia was determined byimmunofluorescence assay and their genetic characterization was achieved by a nested PCR assay targetingthe triosephosphate isomerase gene.Results: All water samples from the river mouth were positive for Giardia, even if the concentration of cystsfluctuated considerably among sampling occasions. Our investigation showed that the Vadduneddu andAltofonte torrents, two influents of the river, were the principal sources of contamination. Moreover, thegenotypes of Vadduneddu torrent were the same as those detected in human wastewater taken from theactivated sludge plant of Monreale city. Assemblages A and B were found in water samples with apredominance of Assemblage A, subtype AII. Assemblage E was only found in a single calf isolate.Conclusions: The data show that the high cyst counts regularly detected in the Oreto river are due tocontamination with wastewater of human origin. This finding is relevant for public health, particularlybecause river water is used for agricultural purposes.
Keywords: Giardia; Oreto River; contamination